Respuesta :
This is how you simplify your equation;
2(4u + 7 ) = 62
8u + 14 = 62
8u + 14 -14 = 62 -14 (subtract 14 on both sides)
8u = 62 -14
8u = 48
u = 48 ÷ 8 (did the inverse operation)
u = 6
2(4u + 7 ) = 62
8u + 14 = 62
8u + 14 -14 = 62 -14 (subtract 14 on both sides)
8u = 62 -14
8u = 48
u = 48 ÷ 8 (did the inverse operation)
u = 6
2(4u+7)= 62
⇒ 4u+7= 62/2 (inverse operation)
⇒ 4u+ 7= 31
⇒ 4u= 31 -7 (inverse operation)
⇒ 4u= 24
⇒ u= 24/4 (inverse operation)
⇒ u= 6
Final answer: u= 6.
⇒ 4u+7= 62/2 (inverse operation)
⇒ 4u+ 7= 31
⇒ 4u= 31 -7 (inverse operation)
⇒ 4u= 24
⇒ u= 24/4 (inverse operation)
⇒ u= 6
Final answer: u= 6.